Development and Validation of RP-HPLC Method for Estimation of Zolmitriptan in Tablet Dosage Forms - Gowri Sankar, D.; Nagesh Babu, A.; Rajeswari, A.; Vamsi Krishna, M. (Asian Journal of Chemistry, 2010)
A rapid, simple and precise reversed phase high performance liquid chromatography (RP-HPLC) method was developed for the estimation of zolmitriptan in tablets. The quantification was carried out using a X-Terra RP C-18 column (150 mm × 4.6 mm i.d., 5 μm particle size) in isocratic mode with mobile phase comprising of phosphate buffer, acetonitrile and methanol in the ratio of 65:15:20 (v/v) at a flow rate of 1 mL/min. The eluent was monitored at 225 nm. The retention time of the drug was 4.278 min. The calibration curve was linear in the concentration range of 5-70 μg/mL and per cent recovery ranged from 99.8-100.08.